FAKTOR INDIVIDUAL DAN KONTEKSTUAL PADA MIGRASI RISEN DI INDONESIA: ANALISIS DATA SURVEI PENDUDUK ANTAR SENSUS 2015 - Bety Atmani M; Agus Joko Pitoyo; Abdur Rofi (Research Centre for Population, Indonesian Institute of Sciences, 2020)
Migration is a complex phenomenon influenced by various factors, including individual, household and contextual factors. The purpose of this study is to determine the factors that influence the decision to migrate, both at the individual and contextual level. The data used are the 2015 Intercensal Population Survey and official statistics of Indonesia published by Badan Pusat Statistik (BPS). The analytical method used is a multilevel binary logistic regression. The analysis results show that age, marital status, education level, work status, education level of the head of the household, number of household members, homeownership, and area of residence affect the decision to migrate among residents aged 15 years and older. Migrants tend to go to regions with higher Gross Domestic Product (GDP) per capita, provincial minimum wage, and Human Development Index (HDI), and lower unemployment rate.